GABA Concentration in the Left Ventral Premotor Cortex Associates With Sensory Hyper-Responsiveness in Autism Spectrum Disorders Without Intellectual Disability - Umesawa, Yumi; Atsumi, Takeshi; Chakrabarty, Mrinmoy; Fukatsu, Reiko; Ide, Masakazu (Frontiers in Neuroscience, 2020)
Individuals with autism spectrum disorder (ASD) often exhibit abnormal processing of sensory inputs from multiple modalities and higher-order cognitive/behavioral response to those inputs. Several lines of evidence suggest that altered γ-aminobutyric acid (GABA), the main inhibitory neurotransmitter in the brain, is a central characteristic of the neurophysiology of ASD. The relationship between GABA in particular brain regions and atypical sensory processing in ASD is poorly understood. We therefore employed 1H magnetic resonance spectroscopy (1H-MRS) to examine whether GABA levels in brain regions critical to higher-order motor and/or multiple sensory functions were associated with abnormal sensory responses in ASD. We evaluated atypical sensory processing with a clinically-validated assessment tool. Furthermore, we measured GABA levels in four regions: one each in the primary visual cortex, the left sensorimotor cortex, the left supplementary motor area (SMA), and the ventral premotor cortex (vPMC). These regions are thought to be involved in executing and coordinating cognitive and behavioral functions in response to multisensory inputs. We found sensory hyper-responsiveness in ASD relative to control participants. We also found reduced GABA concentrations in the left SMA but no differences in other regions of interest between ASD and control participants. A correlation analysis revealed a negative association between left vPMC GABA and the severity of sensory hyper-responsiveness across all participants, and the independent ASD group. These findings suggest that reduced inhibitory neurotransmission (reduced GABA) in a higher-order motor area, which modulates motor commands and integrates multiple sensory modalities, may underlie sensory hyper-responsiveness in ASD.